The Influence of Competence, Compensation, and Communication Skills on Work Productivity at PT Putra Darma Indonesia - Fitria, Fariza; Sari, Nurma; Dita, Rizky Aulia; Ferine, Kiki Farida (Dinasti Publisher, 2026)
Human resource management (HRM) constitutes a critical determinant of a company’s ability to achieve organizational objectives and sustain employee productivity. This study aims to examine the influence of competence, compensation, and communication skills on employee work productivity at PT Putra Darma Indonesia, a company operating in the coffee industry and export sector. The company faces several challenges, including suboptimal employee competence resulting from limited training opportunities, a compensation system that has yet to fully align with employees’ needs and expectations, and inadequate communication skills due to ineffective formal communication channels. This research was conducted to evaluate the extent to which these three variables contribute to employee productivity. The findings reveal that competence does not exert a significant influence on work productivity, whereas compensation and communication skills demonstrate significant effects, with communication skills exhibiting a negative directional relationship. Simultaneously, the three variables collectively influence employee productivity. These findings indicate that the company should optimize its compensation system while also reassessing and strengthening competence development and communication practices to improve employee productivity more effectively.